2019
DOI: 10.1242/dev.182170
|View full text |Cite
|
Sign up to set email alerts
|

Reprogramming: identifying the mechanisms that safeguard cell identity

Abstract: Development and homeostasis rely upon concerted regulatory pathways to establish the specialized cell types needed for tissue function. Once a cell type is specified, the processes that restrict and maintain cell fate are equally important in ensuring tissue integrity. Over the past decade, several approaches to experimentally reprogram cell fate have emerged. Importantly, efforts to improve and understand these approaches have uncovered novel molecular determinants that reinforce lineage commitment and help r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(27 citation statements)
references
References 239 publications
(310 reference statements)
2
25
0
Order By: Relevance
“…has not only increased the number of cell sources for cell type-and patient-specific therapeutic purposes, but also revealed the significant plasticity of the genome of differentiated cells (Brumbaugh et al, 2019;Hochedlinger and Jaenisch, 2015). In particular, the induction of pluripotency by a combination of transcription factors (e.g., Oct4, Sox2, Klf4 and Myc) has shown that the genetic network of a differentiated cell can be disrupted and cause epigenetic modifications driven by both, the forced expression of exogenous genes encoding transcription factors and the culture conditions (Hochedlinger and Jaenisch, 2015).…”
Section: Somatic Cell Reprogramming Mediated By a Combination Of Tranmentioning
confidence: 99%
“…has not only increased the number of cell sources for cell type-and patient-specific therapeutic purposes, but also revealed the significant plasticity of the genome of differentiated cells (Brumbaugh et al, 2019;Hochedlinger and Jaenisch, 2015). In particular, the induction of pluripotency by a combination of transcription factors (e.g., Oct4, Sox2, Klf4 and Myc) has shown that the genetic network of a differentiated cell can be disrupted and cause epigenetic modifications driven by both, the forced expression of exogenous genes encoding transcription factors and the culture conditions (Hochedlinger and Jaenisch, 2015).…”
Section: Somatic Cell Reprogramming Mediated By a Combination Of Tranmentioning
confidence: 99%
“…Together, the cell fate induction experiments described above have revealed roles for both heterochromatin and euchromatin-associated factors in the regulation of cell fate plasticity in several developmental contexts and cell types. Looking beyond C. elegans, chromatin-based mechanisms have also been identified as key barriers to the reprogramming of mammalian cells [reviewed in Brumbaugh et al (2019)]. Robust characterization of the epigenetic mechanisms governing cell fate therefore holds promise to influence advancements in regenerative medicine.…”
Section: Functional Consequences Of Regulation By Chromo Domain Protementioning
confidence: 99%
“…Ectopic expression of four TFs (OCT4, SOX2, KLF4, and c-MYC) can convert somatic cells into iPSCs with the genetic and epigenetic characteristics of stem cells, capable of self-renewing and differentiating into all germ layers in vivo . As somatic cells reprogram, they undergo cellular, transcriptional, metabolic, and epigenetic changes that result in erasure of the somatic program and establishment of pluripotency-defining properties ( Apostolou and Hochedlinger, 2013 ; Brumbaugh et al., 2019 ; Papp and Plath, 2013 ). 3D chromatin architecture is also drastically reorganized during reprogramming, as shown by comparing various somatic cells with the resultant iPSCs, through profiling long-range interactions around specific loci (4C-seq or 5C) ( Apostolou et al., 2013 ; Beagan et al., 2016 ; Denholtz et al., 2013 ; Wei et al., 2013 ) or in a genome-wide fashion by Hi-C ( Krijger et al., 2016 ).…”
Section: Main Textmentioning
confidence: 99%